'Good' Law. (19th June 2015) - Hoadley, Daniel
Abstract: The ever increasing capabilities of online legal research platforms have revolutionised the strategies we adopt in tackling routine research questions. It is now possible, for example, to comprehensively identify later judicial references to any given earlier case at the click of a button. However, we are potentially running the risk of believing that the online platforms are capable of providing us with answers to questions that they are not yet able to deliver. In this short article Daniel Hoadley focuses on the capability of the current spread of online research platforms to answer a frequent and fundamental legal research question: "is this case still good law?"